Generasi Z’s Perception of Dining Experience at Korea Restaurants, South Jakarta - Suheryadi, Heru; Dian Sua Pratama, Bayu; Rahmah Farahdiba, Siti; Elya Rohimi, Upit (Journal of World Science, 2023)
Culinary tourism is a strong attraction and can improve the standard of living of local residents. The strong growth of the Korean food industry proves that Korean food is well received by various circles, one of which is Generation Z. The trend of Korean culture in this era of globalization is very strong so that it easily penetrates into Indonesia, especially South Jakarta. The variety of Korean food choices offered has increased consumers perception of choosing location, atmosphere, and food as an attraction. The restaurant business is now not only delicious food, restaurant business people are now also required to present a memorable dining experience. This study aims to understand the perception of Generation Z on the dining experience at a South Jakarta Korean restaurant. The sampling technique in this study was Generation Z, with 100 respondents. This research is described in 4 perceptual factors, namely motivation, interest, experience, and expectations. The data analysis technique used is descriptive analysis, validity test, and reliability test. Based on the results of the questionnaire distributed, generation Z chose Moon Chicken as their favorite Korean restaurant because it has memorable service. Korean restaurants have a min taste that is not to strong and there is curiosity about the interior design of Korean restaurants, which is different from other restaurant.